Sistem Informasi Komite Lingkungan PT. Bukit Asam Unit Pelabuhan Tarahan - Igit Sabda Ilman; Ridho Sholehurrohman; Taufik Nurhidayat; Rahman Taufiq; Muhaqiqin (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The Environmental Committee Information System of PT. Bukit Asam Tarahan Port Unit is an application that aims to facilitate the management of data and information related to environmental activities in the working area of PT. Bukit Asam Tarahan Port Unit. This application is built using the waterfall method and equipped with features such as recording environmental activity reports, monitoring water and air quality, and managing environmental inventories. The data collection method used in this research is interviews and observations. The results of the study show that the use of this application can facilitate data and information management, as well as help in decision-making related to environmental activities at PT. Bukit Asam Tarahan Port Unit. This application is expected to improve the efficiency and effectiveness of environmental management at PT. Bukit Asam Tarahan Port Unit.